2019
DOI: 10.1007/s13280-019-01191-0
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar status of Arctic ptarmigan: Population dynamics and trends

Abstract: Rock ptarmigan (Lagopus muta) and willow ptarmigan (L. lagopus) are Arctic birds with a circumpolar distribution but there is limited knowledge about their status and trends across their circumpolar distribution. Here, we compiled information from 90 ptarmigan study sites from 7 Arctic countries, where almost half of the sites are still monitored. Rock ptarmigan showed an overall negative trend on Iceland and Greenland, while Svalbard and Newfoundland had positive trends, and no significant trends in Alaska. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 39 publications
0
55
0
1
Order By: Relevance
“…Because our study only lasted two years, we are not able to estimate robustly any between year variation due to stochastic environmental factors or variation in harvest pressure. In addition, recent studies of rock ptarmigan throughout their range has shown that cyclic dynamics is a common feature (Fuglei et al, 2019), suggesting that also demographic rates are likely to fluctuate temporarily. Often, populations inhabiting alpine areas (i.e., high altitudes) have higher survival and lower reproduction compared to populations/species at lower elevations (Sandercock et al, 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our study only lasted two years, we are not able to estimate robustly any between year variation due to stochastic environmental factors or variation in harvest pressure. In addition, recent studies of rock ptarmigan throughout their range has shown that cyclic dynamics is a common feature (Fuglei et al, 2019), suggesting that also demographic rates are likely to fluctuate temporarily. Often, populations inhabiting alpine areas (i.e., high altitudes) have higher survival and lower reproduction compared to populations/species at lower elevations (Sandercock et al, 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In general, alpine populations should be expected to move upward, whereas polar tundra species are expected to conduct latitudinal movements (Lehikoinen et al, 2019). Among the few resident birds in these habitats, the rock ptarmigan (Lagopus muta) has a wide, circumpolar distribution across the northern tundra and high-mountain regions (Storch, 2007;Fuglei et al, 2019). Rock ptarmigan as a species is expected to be strongly affected by climate change (Booms et al, 2012;Revermann et al, 2012;Hansen et al, 2013), and is therefore a suitable model species for examining climate change effects on alpine wildlife populations.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, circumpolar terrestrial bird FEC-attribute trends and monitoring coverage are discussed in three papers: Fuglei et al (2020) focused on the Arctic-resident herbivores, rock ptarmigans (Lagopus muta), and willow ptarmigans (Lagopus lagopus); Franke et al 2020focused on top predators, the Arctic-resident gyrfalcon (Falco rusticolus), and the migrant peregrine falcon (Falco peregrinus); and Smith et al (2020) reviewed the status of all main terrestrial bird populations (88 species included) according to functional groups (herbivore, insectivore, etc. ), and 'flyways' (main migration routes) utilized by different populations.…”
Section: Birdsmentioning
confidence: 99%
“…Birds: Biodiversity status Fuglei et al (2020) compiled the first circumpolar synthesis of ptarmigan trends and added considerable broad-scale understanding of ptarmigan population dynamics. For rock ptarmigan, there was a significant, declining trend in density in 10 of 31 monitoring sites (time series), while a significant increase in density was found at five sites.…”
Section: Birdsmentioning
confidence: 99%
See 1 more Smart Citation